(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2014)
Armenian (Noyemberyan region) zeolite bearing tuff absorption-desorption kinetic has been studied. It has been found out that Armenian zeolite bearing tuff has the ability of separating heavy water from HTO+H2O system. The amount of sorbent heavy water increases with increasing zeolite content in the tuff. Desorption of heavy water from zeolitic tuff depends on zeolite phase content, particle size, surrounding liquid chemicals and temperature. Temperature decrease of the surrounding liquid (from 90°C to 25℃ ) and the increase of sorbent particle size (from 20 to 80 mkm) reduces heavy water desorption. Acid environment causes complete desorption of heavy water from zeolitic tuff.